BANK SYARIAH SEBAGAI ALTERNATIF PEMBIAYAAN UNTUK MENINGKATKAN EKONOMI UMAT - Nada Rakhima Salsabila; Achmad Diny Hidayatullah; Nur Syafiqah Hussin (Universitas Muhammadiyah Prof Dr Hamka, 2023)
The development of an increasingly advanced era encourages public awareness of religious values to be higher. Almost all elements of life feel this change, including the economic sector. In describing this trend, Islamic banks are present and spread across various districts and cities in Indonesia. According to data from the Financial Services Authority (OJK), as of January 2021, there are 34 sharia banking businesses in Indonesia. The purpose of this study is to describe the trends and impacts of sharia-based economic financing. The research method used is descriptive, comparative, and literature study. The results of the study show that sharia-based economic financing in an Islamic perspective is able to improve the people's economy in a more just and sustainable manner. Islamic banks provide financing according to Islamic principles and banking services such as investment and Islamic insurance.